EFEKTIFITAS PENDEKATAN SANTIFIK DALAM MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR RANAH KOGNITIF SISWA KELAS IV (Study Eksperimen di MI Maulana Maghribi Pundong Bantul) - Muhammad Asrofi (MAMBA'UL 'ULUM, 2022)
This writing is motivated by the lecture method that puts forward the teacher center principle which is often used by teachers who have the potential to be a source of lack of student activity in science learning at MI Maulana Maghribi. An innovative approach to learning by prioritizing the role of students is possible to provide space for student activity. The scientific approach which is motivated by teaching and learning activities that are less passive in providing a stimulus for student activity and changing the paradigm from teacher oriented to student oriented is possible to bring about changes both in relation to learning outcomes and student activity. This writing is quantified using a quasi-experimental design with one group pretest posttest design. This writing aims to reveal the effectiveness of the application of the scientific approach in increasing the activeness and learning outcomes of science subjects in grade IV at MI Maulana Maghribi, Bantul, Yogyakarta. The results of the descriptive test reveal that learning with a scientific approach has not been able to increase student learning activities optimally. The results of the different test of learning outcomes between before and after the application of the scientific approach in learning got a t-hit coefficient = 5.589 with p ≤ 0.05 (significant), learning outcomes after application (x̄ = 67.27) were higher than before the application (x̄ = 48.52). Based on these results, it can be concluded that the application of a scientific approach to science lessons for fourth grade students at MI Maulana Maghribi Pundong Bantul, Yogyakarta on the 2015/2016 Academic Year: 1) Not optimal in increasing student activity in science learning, 2) Successfully improving science learning outcomes.